If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 70 + -9x = 43 Solving 70 + -9x = 43 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-70' to each side of the equation. 70 + -70 + -9x = 43 + -70 Combine like terms: 70 + -70 = 0 0 + -9x = 43 + -70 -9x = 43 + -70 Combine like terms: 43 + -70 = -27 -9x = -27 Divide each side by '-9'. x = 3 Simplifying x = 3
| 3x+7=55 | | e+21.94=6.3 | | 43+16c-18d+56c+16d= | | y-9.68=-4.5 | | 94=60+2x | | 6x+-10=32 | | 0.24x=18.26 | | 100=2x+3+51 | | 5x+7=-19-8x | | 2n+6(n-7)= | | 5x-4=-119 | | 8+3[5+2(12-8)-1]= | | 9y-36x=90 | | 3x+33=5x-9 | | y+2y+3z= | | 12x-7=137 | | 163-4x=41x+23 | | 4x=x-11 | | 14-8x=44-22x | | 5x+12=-114-9x | | 5x+12=-144-9x | | 97-4x=2x+7 | | 4n-40=7(2n+2) | | 84-4x=7x+18 | | 9+12x=53+x | | 71-5x=7x+23 | | t^3-2t^2-9t+18=0 | | -9+x=12 | | -59-10x=10x+21 | | 6x+9=-126-9x | | -24-3x=12-9x | | 12(2x-3)=6x |